A comparison of solving fractional programming problems using the neglected variables' complement method and the complement method (Journal of the College of Basic Education, 2022)
The aim of this work to give method to solve linear fractional programming using a complementary slackness method and comparing the solution with complementary method to reach the global optimal solution.